2021
DOI: 10.29333/pr/10963
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Combined Effects of Motivation, Learning and Personality Traits on Academic Performance

Abstract: Domains of motivation, learning and personality traits (MLP) have emerged as vital constructs in studies of academic performance. Although there are abundant studies on the relationships of the three aforementioned dimensions on performance, no systematic synthesis of the empirical literature has been done regarding how three determinants jointly influence academic performance. Random-effects meta-regression analysis with a restricted maximum likelihood estimator is applied to 54 papers with 344 estimates. Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 205 publications
1
6
0
Order By: Relevance
“…As the research team was unable to obtain data related to the students’ academic performances before the intervention, the motivational level of the students was used to serve as the covariate of the study. Previous studies have shown consistent findings where motivation level was highly correlated to academic achievements (Broussard & Garrison, 2009 ; Nauzeer & Jaunky, 2021 ).…”
Section: Data Analysis and Resultssupporting
confidence: 64%
“…As the research team was unable to obtain data related to the students’ academic performances before the intervention, the motivational level of the students was used to serve as the covariate of the study. Previous studies have shown consistent findings where motivation level was highly correlated to academic achievements (Broussard & Garrison, 2009 ; Nauzeer & Jaunky, 2021 ).…”
Section: Data Analysis and Resultssupporting
confidence: 64%
“…The final set of meta-regression analysis variables relates to various dimensions of the publication process. Differences between published and unpublished studies are accounted for via the variable published (Nauzeer and Jaunky, 2021).…”
Section: Publication Statusmentioning
confidence: 99%
“…Student interest in mathematics enhances their desire to acquire mathematics knowledge, thereby enhancing mathematics performance (Reeve et al, 2015). Personality traits may also influence students' performance academic outcomes (Nauzeer & Jaunky, 2021;Röllke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%